ANALISIS KETERAMPILAN BERMAIN ALAT MUSIK ANGKLUNG PADA SISWA SEKOLAH DASAR - Siska Kusumawardani; Nanda Nur Aulia (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
The purpose of this study was to analyze and describe the skills of playing angklung musical instruments in elementary school children. The research method in this research is descriptive research with observation, documentation and interview data. The research was conducted at SD Private Syafana Islamic School with the subjects studied were 10 children who were a combination of low classes, namely class 1,2,3. Data analysis using descriptive-qualitative analysis. The results showed that the skills to play angklung consisted of 1) preparation consisting of recruiting children to enter extra angklung musical instruments. 2) Preparation, formulate learning objectives to play angklung, determine methods in playing angklung skills 3) implementation. a) the teacher conveys the learning objectives and provides material about the angklung musical instrument b) the teacher demonstrates the angklung, how to hold, how to play the resulting tone. c). given training using angklung and 4) evaluation by holding an art performance playing angklung which is held in schools through audience appreciation.